Randomized multicentre feasibility trial of intermediate care versus standard ward care after emergency abdominal surgery (InCare trial). Issue 6 (18th March 2015) - Vester‐Andersen, M.; Waldau, T.; Wetterslev, J.; Møller, M. H.; Rosenberg, J.; Jørgensen, L. N.; Jakobsen, J. C.; Møller, A. M.; the InCare trial group; Gillesberg, I. E.; Jakobsen, H. L.; Hansen, E. G.; et al.
<x xml:space="preserve">Abstract</x> Background Emergency abdominal surgery carries a considerable risk of death and postoperative complications. Early detection and timely management of complications may reduce mortality. The aim was to evaluate the effect and feasibility of intermediate care compared with standard ward care in patients who had emergency abdominal surgery. Methods This was a randomized clinical trial carried out in seven Danish hospitals. Eligible for inclusion were patients with an Acute Physiology And Chronic Health Evaluation (APACHE) II score of at least 10 who were ready to be transferred to the surgical ward within 24 h of emergency abdominal surgery. Participants were randomized to either intermediate care or standard surgical ward care after surgery. The primary outcome was 30‐day mortality. Results In total, 286 patients were included in the modified intention‐to‐treat analysis. The trial was terminated after the interim analysis owing to slow recruitment and a lower than expected mortality rate. Eleven (7·6 per cent) of 144 patients assigned to intermediate care and 12 (8·5 per cent) of 142 patients assigned to ward care died within 30 days of surgery (odds ratio 0·91, 95 per cent c.i. 0·38 to 2·16; P = 0·828). Thirty (20·8 per cent) of 144 patients assigned to intermediate care and 37 (26·1 per cent) of 142 assigned to ward care died within the total observation period (hazard ratio 0·78, 95 per cent c.i. 0·48 to 1·26; P = 0·310). Conclusion Postoperative intermediate care had no statistically significant effect on 30‐day mortality after emergency abdominal surgery, nor any effect on secondary outcomes. The trial was stopped prematurely owing to slow recruitment and a much lower than expected mortality rate among the enrolled patients. Registration number: NCT01209663 (http://www.clinicaltrials.gov).